2003
DOI: 10.1074/jbc.m303161200
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Heat Shock Protein 60 Does Not Induce the Release of Tumor Necrosis Factor α from Murine Macrophages

Abstract: Recent studies have shown that commercially available recombinant human heat shock protein 60 (rhHSP60) could induce tumor necrosis factor ␣ (TNF-␣) release from macrophages and monocytes in a manner similar to that of lipopolysaccharide (LPS), e.g. via CD14 and Toll-like receptor 4 complex-mediated signal transduction pathway. In this study, we demonstrated that a highly purified rhHSP60 preparation with low endotoxin activity (designated rhHSP60-1) was unable to induce TNF-␣ release from murine macrophages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
171
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(182 citation statements)
references
References 48 publications
(53 reference statements)
9
171
2
Order By: Relevance
“…In light of the findings presented here for microglia, and consistent with what has been previously suggested in the macrophage/monocyte literature (Gao and Tsan, 2003b), we propose that the following considerations be taken into account for future studies involving microglia. First, whenever possible, pharmaceutical-grade, endotoxin-free reagents be used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In light of the findings presented here for microglia, and consistent with what has been previously suggested in the macrophage/monocyte literature (Gao and Tsan, 2003b), we propose that the following considerations be taken into account for future studies involving microglia. First, whenever possible, pharmaceutical-grade, endotoxin-free reagents be used.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the findings not only confirmed the functionally significant levels of LPS contamination in the plasmaderived thrombin preparations, but also demonstrated the scope and severity of the LPS contamination problem for a host of other factors and compounds relevant to CNS pathophysiology. The results are also consistent with several isolated findings from the immunology literature describing the effects of LPS contamination on macrophage/ monocyte activation by a few selected commercial-grade protein preparations including heat-shock protein-60 (Gao and Tsan, 2003b), −70 (Gao and Tsan, 2003) and the lectin pokeweed mitogen (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…18 19 However, such reports have been questioned by studies indicating that proinflammatory activity of HSP via such receptors was solely due to bacterial contaminants. [20][21][22] Even though this cannot be entirely excluded, because regular tests to exclude that contamination by lipopolysaccharide (LPS) is responsible for the observed effects (such as polymyxin B preincubation and/or protein denaturing by boiling HSP), might not affect all other bacterial compounds, several reports show that highly purified HSP can still activate dendritic cells and macrophages. For example, HSP derived from murine liver and kidney has been shown to be able to activate dendritic cells and macrophages.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Numerous investigations have shown that both HSP60 and HSP70 potently provoke proinflammatory responses (29,(33)(34)(35)(36), but two recent studies of murine M have suggested that the TNF-␣-inducing activities of recombinant HSP preparations are due entirely to contaminating LPS (37,38). Accordingly, to clarify the role of HSP in activation of human M , we used highly purified recombinant HSP60 and HSP70 preparations (ESP-540 and ESP-555; StressGen Biotechnologies, Victoria, Canada), which contain low levels of endotoxin and do not induce release of TNF-␣ from murine M (37,38).…”
Section: Figurementioning
confidence: 99%
“…Accordingly, to clarify the role of HSP in activation of human M , we used highly purified recombinant HSP60 and HSP70 preparations (ESP-540 and ESP-555; StressGen Biotechnologies, Victoria, Canada), which contain low levels of endotoxin and do not induce release of TNF-␣ from murine M (37,38). In our experiments, both recombinant HSP60 and HSP70, at concentrations up to 5 g/ml, caused only a slight increase in TNF-␣ production by human M (Fig.…”
Section: Figurementioning
confidence: 99%